2017
DOI: 10.3389/fphys.2017.01074
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training with Co-ingestion of Anti-inflammatory Drugs Attenuates Mitochondrial Function

Abstract: Aim: The current study aimed to examine the effects of resistance exercise with concomitant consumption of high vs. low daily doses of non-steroidal anti-inflammatory drugs (NSAIDs) on mitochondrial oxidative phosphorylation in skeletal muscle. As a secondary aim, we compared the effects of eccentric overload with conventional training.Methods: Twenty participants were randomized to either a group taking high doses (3 × 400 mg/day) of ibuprofen (IBU; 27 ± 5 year; n = 11) or a group ingesting a low dose (1 × 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…This is interesting given that we ( Roberts et al, 2018 ; Haun et al, 2019a ) and others ( Tesch et al, 1987 ) have reported RT may promote mitochondrial dilution as evidenced through a decrease in CS activity. Moreover, limited evidence suggests that RT increases CS activity ( Tang et al, 2006 ; Cardinale et al, 2017 ). It is difficult to reconcile why the current data show that CON increased mitochondrial volume, whereas VAR did not.…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting given that we ( Roberts et al, 2018 ; Haun et al, 2019a ) and others ( Tesch et al, 1987 ) have reported RT may promote mitochondrial dilution as evidenced through a decrease in CS activity. Moreover, limited evidence suggests that RT increases CS activity ( Tang et al, 2006 ; Cardinale et al, 2017 ). It is difficult to reconcile why the current data show that CON increased mitochondrial volume, whereas VAR did not.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of NSAIDs on mitochondrial biogenesis indices have also been examined . Unexpectedly, we noted decreased mitochondrial phosphorylation in response to the resistance training intervention, with no effect of the high or lower NSAID intake.…”
Section: Training Adaptationsmentioning
confidence: 72%
“…Drugs that affect muscle adaptation to exercise (mitochondrial functionality, muscle protein synthesis) 6-hydroxy-2,5,7,8-tetramethylchromane-2carboxylic acid (Trolox) [ acetylsalicylic acid [14] ibuprofen [14] acetaminophen [15]…”
Section: Drugs or Supplements That Have A Synergistic Effect With Exercise On The Biogenesis And Improvement Of Mitochondrial Functionsmentioning
confidence: 99%
“…Co-administration of anti-inflammatory drugs (acetylsalicylic acid, ibuprofen) with resistance training results in reduced mitochondrial function [14]. It is reasonable to assume that these organelles become more vulnerable to COVID- 19 damage.…”
Section: Introductionmentioning
confidence: 99%